Apprenticeship in drinking: learning to play and binge drinking on a college campus - Hundersmarck, Steven F. (Applied psychology in criminal justice, 2015)
Binge drinking on the college campus and the problems associated with it carry a high cost. Problems associated with alcohol abuse on the college campus include death, injury, property damage and sexual assaults. These issues continue to plague police and college administration officials. To date, most research has focused on individual factors associated with the problem of binge drinking. In this paper the author used both quantitative and qualitative methodology to research binge drinking among college students on a university campus. The results obtained through observations and structured interviews show that students enter a developmental model of drinking beginning most often in their freshman year that continues into their senior year. Freshman students entered into an "apprenticeship of drinking" as they progressed from apprentice to upperclassman expert by learning the social and cultural norms and values of drinking on campus. For purposes of this paper binge drinking was defined as 4-5 drinks in the same setting or occasion.